2006
DOI: 10.4049/jimmunol.177.9.6281
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Immunoglobulin Receptor in Intestinal Immune Defense against the Lumen-Dwelling Protozoan ParasiteGiardia

Abstract: The polymeric Ig receptor (pIgR) is conserved in mammals and has an avian homologue, suggesting evolutionarily important functions in vertebrates. It transports multimeric IgA and IgM across polarized epithelia and is highly expressed in the intestine, yet little direct evidence exists for its importance in defense against common enteric pathogens. In this study, we demonstrate that pIgR can play a critical role in intestinal defense against the lumen-dwelling protozoan parasite Giardia, a leading cause of dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 69 publications
3
80
1
1
Order By: Relevance
“…We have also recently shown that the host response towards Giardia of differentiated Caco-2 cells is partly mediated by soluble factor(s) [8]. The secreted proteins we identify here are immunodominant in human infections [29,36] and experimental mouse infections [13]. The targeting of secreted giardial proteins for immunoneutralization may thus represent a useful therapeutic strategy, aimed at treating or preventing Giardia infections.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…We have also recently shown that the host response towards Giardia of differentiated Caco-2 cells is partly mediated by soluble factor(s) [8]. The secreted proteins we identify here are immunodominant in human infections [29,36] and experimental mouse infections [13]. The targeting of secreted giardial proteins for immunoneutralization may thus represent a useful therapeutic strategy, aimed at treating or preventing Giardia infections.…”
Section: Discussionmentioning
confidence: 67%
“…In vitro interaction models for G. lamblia and intestinal cells are well established [7][8][9][10][11], as are rodent models [12][13][14] and this has increased the knowledge of the infection [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Free SC can bind to several bacterial proteins, such as colonization factor antigen (Oliveira et al, 2001), Clostridium difficile toxin A (Dallas and Rolfe, 1998), and Streptococcus pneumoniae surface protein C (PspC) (Hammerschmidt et al, 2000). High expression of SC is considered to play an important role in limiting the inflammatory response (Davids et al, 2006;Giugliano et al, 1995;Dallas et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Fax: 8624-22703576. key defense against enteropathogenic Escherichia coli (Araújo et al, 2001), and can inhibit Salmonella typhimurium adhesion to HeLa cells (Bessler et al, 2006). Increasing evidence indicates that high SC expression is important in limiting the inflammatory response to bacterial and viral products, via the antiinflammatory function of SC (Davids et al, 2006;Giugliano et al, 1995;Dallas et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…SC is a nonspecific scavenger of microorganisms and plays a key role in protecting and balancing the intestinal mucous membrane in limiting the inflammation process (1). SC is a key defense to bacteria (2-5) and parasites (6). Moreover, SC can play a critical role in the immune neutralization of the Cholera toxin (7).…”
Section: Kratak Sadr`ajmentioning
confidence: 99%